THE DEVELOPMENT OF THREE DIMENSIONAL ANIMATION FILM FOR CHARACTER EDUCATION MEDIA IN ELEMENTARY SCHOOL - Riyana, Cepi (EDUTECH, 2015)
Abstract. The formation of character is one of the national education goals. Article 1 of the 2003 Education Law states that among the objectives of national education is to develop the potential of learners to have intelligence, personality and noble character. Currently karakterbangsa strengthening of the strategic priorities of national education progra, given the state of the nation must be returned to the characterization of identity bangsa.Berbagai efforts should be made to build character education, including through modeling (modeling) characters through 3D animations Fim impressions. The strength of this medium is its appeal capable mengypnosis children so charges can be internalized character education in children. The purpose of this research is to "develop Animation 3D Virtual Reality for Education Character in elementary school," This study uses the Research Development (R D) through the stages: (1) analysis of the needs of the Media, (2) Media Development, (3) Validation and Product dissemination. Subjects were students of primary schools, with three locations in West Java (Bandung, Cimahi, Bandung regency). The results of this study indicate that the model is designed with ABC animation (animation character building) a positive impact on habituation as a first step to the formation of character in elementary students.Keywords: Character Education, Film 3D AnimationAbstrak. Pembentukan karakter merupakan salah satu tujuan pendidikan nasional. Pasal 1 UU Sisdiknas tahun 2003 menyatakan bahwa di antara tujuan pendidikan nasional adalah mengembangkan potensi peserta didik untuk memiliki kecerdasan, kepribadian dan akhlak mulia. Saat ini penguatan terhadap karakter bangsa menjadi prioritas program strategis pendidikan nasional, mengingat kondisi bangsa harus dikembalikan pada karakterisasi jati diri bangsa. Berbagai upaya perlu dilakukan untuk membangun pendidikan karakter, diantaranya melalui pemodelan (modeling) karakter melalui tayangan Fim Animasi 3D. Kekuatan media ini adalah daya tariknya yang mampu menghipnosis anak sehingga muatan-muatan pendidikan karakter dapat diinternalisasi pada diri anak. Tujuan Penelitian ini adalah â€œmengembangkan Film Animasi 3D untuk Pendidikan Karater di Sekolah Dasarâ€, Penelitian ini menggunakan metode Research Development (RD) melalui tahapan : (1) Analisis kebutuhan Media, (2) Pengembangan Media , (3) Validasi dan Diseminasi Produk. Subyek penelitian adalah siswa SD, dengan lokasi di tiga wilayah Jawa Barat (Cimahi, Kabupaten Bandung Barat dan Cianjur). Hasil penelitian ini menunjukkan bahwa model animasi yang didesain dengan ABC (animation character building) berdampak pada pembiasaan positif sebagai langkah awal untuk pembentukan karakter pada siswa SD.Kata Kunci : Pendidikan Karakter, Film 3D Animasi